1997
DOI: 10.5014/ajot.51.7.589
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of a Problem-Based Learning Course

Abstract: Within occupational therapy education, there has been increased attention to curricula and courses that emphasize problem solving, clinical reasoning, and synthesis of information across traditional discipline-specific boundaries. This article describes the development, implementation, and outcomes of a problem-based learning course entitled Selected Cases in Occupational Therapy. The course was designed to help students to integrate the various elements of a specific occupational therapy curriculum and to enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…Students and staff are usually favourable about the skills acquired during PBL (e.g. Bligh et al, 2000;Hammel et al, 1999;Kaufman & Mann, 1996;Stern, 1997). PBL methods have been found to attract applicants to a particular occupational therapy course, with 72% of applicants indicating that this was a 'very' or 'fairly' important reason for choice (Craik et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Students and staff are usually favourable about the skills acquired during PBL (e.g. Bligh et al, 2000;Hammel et al, 1999;Kaufman & Mann, 1996;Stern, 1997). PBL methods have been found to attract applicants to a particular occupational therapy course, with 72% of applicants indicating that this was a 'very' or 'fairly' important reason for choice (Craik et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Wittman and Velde (2002) propose that critical thinking skills are necessary to the profession's ability to provide culturally appropriate services. Problem-based learning (PBL) is one educational method for achieving critical thinking skills, yet minimal evidence exists in the research literature to assess critical thinking as an outcome of PBL (Foley et al, 1997;Friedman et al, 1990;Stern, 1997). Royeen (1995) and Stern (1997) identified a relationship between critical thinking and clinical reasoning.…”
Section: Introductionmentioning
confidence: 99%
“…Problem-based learning (PBL) is one educational method for achieving critical thinking skills, yet minimal evidence exists in the research literature to assess critical thinking as an outcome of PBL (Foley et al, 1997;Friedman et al, 1990;Stern, 1997). Royeen (1995) and Stern (1997) identified a relationship between critical thinking and clinical reasoning. Therefore, in this study we investigated the level of critical thinking demonstrated by members of two cohort groups of occupational therapy students completing their baccalaureate degrees and evaluated the use of guided reciprocal peer questioning (GRPQ) proposed by King in 1990 as a way to increase students' critical thinking test scores and their ability to generate questions that reflect their critical thinking capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Using a multiyear qualitative design, Hammel et al (1999) examined student perspectives ( n = 154) on problem‐based learning and concluded that a PBL approach enhanced the development of information management, communication, critical reasoning, and team‐building skills. Stern (1997) reported similar benefits of PBL from the student perspective in relation to professional behaviour, integration of information, and clinical reasoning; however, these results were based on one new PBL course and a small sample size of 11 students. According to Hammel et al (1999) , student concerns with PBL relate to time management, information access, instructor expectations, and coping with ambiguity of knowledge.…”
Section: Inputmentioning
confidence: 86%